Internet memes as knowledge practice in social movements: Rethinking Economics' delegitimization of economists. (December 2022) - Harbo, Tenna Foustad
Abstract: Following della Porta and Pavan (2017), progressive social movements act as laboratories of innovation and knowledge creation in their pursuit to reform or resist societal structures. Simultaneously, movements are increasingly dependent upon digital tools and platforms, including social media, in their effort to organize, diffuse and saturate their agendas. Through an analysis of Rethinking Economics' internet memes from 2019, the article investigates how internet memes contribute to a construction of the movement's collective self. Memes characterize a relatively new form of online culture that offers affordable venues of expression, engagement and participation especially apt for bottom-up initiatives with limited funds. My focus is on the internet memes' potential for deliberation and knowledge exchange; essentially their potential as supplementary knowledge practice. The article analyzes the narratives and legitimation strategies embedded in Rethinking Economics' internet memes by using Van Leeuwen's (2007) framework. The study suggests that internet memes' distilled communicative qualities qualify them as informal venues for confrontation and learning, in which local movement identification and positionality are both developed, sustained and evaluated.